Chapter Conclusioni - Mastronardi, Luigi (Studi e saggi, 2020)
The present text includes some conceptual maps, aimed at defining the potential role of Community-based cooperatives in revitalising Italian inner areas. The conclusions show the great importance of these cooperatives, which are considered as a key factor in favouring local development, and in arresting demographic decline in marginal areas. Though based on the results obtained with respect to Molise region, these findings can be extended to any other Italian inner area.